Optical Microscope Rehabilitation Nursing Study of Anterior Cruciate Ligament Injury through Lateral Knee Incision Based on Medical Internet of Things - Liping Liu; Nan Chang; Shihong Li; Peipei Gong; Junhua Wang (Applied Bionics and Biomechanics)
With the high development of sports, football has attracted more and more attention from the public. However, the hot competition has made football players undergo high-intensity training, and the risk of injury caused by training is also increasing. Lateral incision knee ACL injury is one of the most common types of injuries in football players, which has a serious impact on the athlete’s physiology and daily training. The comprehensive, multi-level, convenient and fast medical system brought by the medical Internet of Things has become the growing demand of the medical industry. Based on the medical Internet of Things, this paper studies the rehabilitation nursing of football players’ ACL injury by lateral cutting and running combined with optical microscope. In this paper, 36 male and female football players were selected for group experiments, and the landing and peak torque indexes of the experimental group and the control group of male and female athletes were analyzed under the observation of an optical microscope. Group (P <0.05), coxa valgus (P <0.01), internal rotation and knee valgus angles were greater than those in the EM group. And the peak hip flexion angle and knee valgus moment in NF group were lower than those in EF group (P <0.05). After 12 weeks of rehabilitation training, there was a significant difference in the Q/H joint contraction index between the REF group and the CON group (P <0.05), and there was no statistical difference in the other groups. After 12 weeks of rehabilitation training, there was a significant difference in the Q/H joint contraction index between the REF group and the CON group (P <0.05), and there was no statistical difference in the other groups. That is to say, after the systematic rehabilitation training proposed in this paper, the joint contraction performance of the hamstrings/quadriceps in the REF group has been significantly improved. This shows that the rehabilitation nursing under the optical microscope based on the medical Internet of Things has a good effect on the rehabilitation of the football player’s side-cut running knee joint ACL injury.